Strategi Pembelajaran Aqidah Akhlak Di MA Bahrul ‘Ulum Perak Jombang - Sholihah, Siti; Waqfin, Mohammad Saat Ibnu (Universitas KH. A. Wahab Hasbullah, 2023)
Learning strategies are one of the efforts that can be made to improve the quality of education. During the Covid19 pandemic, learning activities were carried out online. After the Covid19 pandemic, teaching and learning activities were carried out face to face. But it is necessary to develop learning strategies for each subject. The focus of the research here is on the Aqidah Akhlak subject, because it is a very important moral lesson for students, especially in madrasa-based schools. So the researchers conducted research at MA Bahrul Ulum Perak Jombang to find out the learning strategies of Aqidah Akhlak and the supporting and inhibiting factors of learning activities in class.